Características Microbiológicas das Infecções Urinárias de Origem Comunitária em Mulheres - Maciel, Janeslane Ferreira (2015)
The urinary tract infection (UTI) is very common, and Gram-negative bacilli mainly cause it. One of rational forms of influence treatment, and reduce the uncertainty in the empirical treatment is knowledge of regional epidemiology and the susceptibility to antimicrobial agents available in the health care network. The objective of this study was to describe the epidemiological characteristics of urinary infections original from Communities in women, the main microorganisms isolated from urine cultures and patterns of resistance to commonly used antimicrobials. Epidemiological study, descriptive, cross-sectional, retrospective using urine cultures and antibiograms reports, carried out in private laboratories located in the city of Goiânia, in the period from 2011 to 2014. There were 92.474 reports which were analyzed from January 2011 to December 2014, the prevalence of positive urine culture was 8.0% (n = 7.404), women represented 84.9% (n = 6.286) of the positive urine cultures in the age group between 35-64 years, and the E. coli (73.8%) the main organism responsible for UTIs. The highest percentage of resistance to E. coli was ampicillin (51,3%), cephalothin (31,0%), trimethoprim (26,5%) and quinolone (nalidixic acid, ciprofloxacina and norfloxacina). Gram-positive were more significant resistance to clindamycin and erythromycin.